Critical Success Factors Involved in the Launch of a New Product in National and International Market: Focus on Indian Paint Companies - Goel, Akanksha (2008)
This research seeks to extend the earlier work done by various researchers and authors that examined the factors involved in the new product launch. In particular, the critical success factors involved in new product launch and the internationalization of the firm to launch the product in the foreign market is examined. The research is done in the context of the Indian Paint industry.